Current options in aerosolised drug therapy for children receiving respiratory support. (5th September 2017) - Trend, S.; von Ungern‐Sternberg, B. S.; Devadason, S. G.; Schultz, A.; Everard, M. L.
Summary: Inhalation of aerosolised medications are the mainstay of treatment for a number of chronic lung diseases and have several advantages over systemically‐administered medications. These include more rapid onset of action for drugs such as β‐adrenergic agonists when compared with oral medication, high luminal doses for inhaled antibiotics when used to treat endobronchial infection, and an improved therapeutic index compared with systemic delivery for these and other classes of drugs such as corticosteroids. The use of aerosolised drugs to treat patients whose tracheas are intubated is less well established, in part because systemic delivery via the intravenous route can be a simpler alternative for many drugs. Consequently, research in this area is largely limited to a number of in vitro studies and very few clinical trials. Unfortunately, a lack of focus in this area has resulted in a number of practices which at best are ineffective, and at worst dangerous for the patient. Although there have been some attempts to re‐invigorate research in order to improve delivery systems, current devices are, to a great extent, based on long‐standing technology developed more than 50 years ago. In this review, we explore current knowledge and provide guidance as to when and how the inhaled route may be of value when treating patients whose tracheas are intubated, and we set out the challenges facing those attempting to advance the topic. We conclude by reviewing current areas of interest that may lead to more effective and widespread use of aerosols in the treatment of intubated patients.